Notas sobre el espanol de América: entorno y contexto en El héroe discreto de Mario Vargas Llosa - Hernández, Humberto (Verba hispanica, 2014)
It is commonly agreed that the teaching and learning of a mother tongue or foreign language must be based on the use of all kinds of oral or written texts, for it is these texts that clearly evince the vitality and complexities of a language. The undoubted quality and topicality of El héroe discreto are reasons enough to make a linguistic analysis of this novel since it will yield interesting lexical and morphological materials for the teaching and learning of one of the most extended varieties of the Spanish language. The aim of this article therefore is to present the results of such an analysis with the hope that they can help readers of the novel to fully understand its content as well as to increase their vocabulary and grammatical competence.
Keywords: učenje jezika; Spanish; španščina; ameriška španščina; leksikografija; lexicography; slovnica; grammar